PENGARUH LINGKUNGAN BELAJAR DI SEKOLAH DAN MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS KELAS VII SEMESTER GENAP SMP NEGERI 1 BESUKI TAHUN PELAJARAN 2017/2018 - Miftahus Surur (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
The purpose of this study was to determine the effect of the learning environment in schools and achievement motivation on student learning outcomes in social studies subjects for class VII even semester of SMP Negeri 1 Besuki in the 2017/2018 academic year. In this study, the research design used was ex post fact. The method of determining the location in this study uses a purposive sampling area. the method of determining the sample is simple random sampling method. Methods of data collection in this study using a questionnaire or questionnaire, documentation, observation, interviews. The data analysis used is instrument test and regression analysis test. The conclusion of this study is that there is an influence between the Learning Environment in Schools and Achievement Motivation on the Learning Outcomes of students in Social Studies subjects for class VII Even Semester SMP Negeri 1 Besuki in the 2017/2018 academic year.